Description of the Donkey in Galician Society: Galician Figurative Expressions that Portray this Animal - González Pereira, Andrea (Madrygal. Revista de Estudios Gallegos, 2021)
The present study, which is part of a broader phraseological investigation, is an analysis of 72 Galician figurative expressions constructed with the animal reference of donkey. We start from the idea that the human being conceptualizes certain situations in his daily life, which are often abstract for him, through figurative language. The references of the animal world occupy an important place in the creation of figurative expressions, in which the human being is usually animalized to, in this way, understand better certain realities. Through the analysis of these expressions, extracted from both general and specialized Galician lexicographic works and from the oral language, we intend to know the valuation that the Galicians make of the donkey, focused on three thematic areas: the characterization of the animal (both physical and moral), his relations with other animals and with the human being and the historical valuation of it in Galician society. In general, negative type assessments occupy an important place in the characterization of the donkey, while positive and neutral assessments have a lower percentage of appearance.